Novel pain management strategy for uterine fibroid embolization - Elaine Ho; Kiat Tsong Tan (CVIR Endovascular)
Abstract Background Uterine fibroid embolization can be associated with significant pain due to fibroid ischemia and interventions of the procedure itself. Fentanyl and midazolam are commonly provided for sedation and pain relief, but are not tolerated by all patients. This report outlines a novel pain management strategy for uterine fibroid embolization in a patient who could not receive either opioids or benzodiazepines. Methods A 51 year old woman presenting with menorrhagia due to uterine fibroids was referred to interventional radiology for embolization. She was allergic to most opiates and had previously become agitated with IV midazolam, resulting in termination of a previous attempt at embolization. Thus, a combination of three analgesic modalities was used: intraarterial ropivacaine in the uterine arteries, superior hypogastric nerve block with ropivacaine, and intravenous acetaminophen. The patient underwent successful embolization and reported only intermittent pain of 1–2 out of 10 intensity. Discussion This combined analgesic cocktail represents a novel alternative to traditional sedation for uterine fibroid embolization and may serve as a viable option for patients with similar contraindications.